Optical laminates and image display devices

JP7933790B2Active Publication Date: 2026-10-13NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023559865
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-15
Filing Date
2022-11-09
Publication Date
2026-10-13
Estimated Expiration
2042-11-09

AI Technical Summary

Benefits of technology

【0008】 本発明の実施形態による画像表示装置は、表示素子の視認側に2つの偏光子が同軸で積層され、その間に印刷層が配置された構成を有する。このような構成を採用することにより、表示領域の輝度を大きく低下させることなく、非表示時における表示領域と非表示領域との外観の違いを認識し難くすることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933790000002
    Figure 0007933790000002
  • Figure 0007933790000003
    Figure 0007933790000003
  • Figure 0007933790000004
    Figure 0007933790000004
Patent Text Reader

Abstract

The present invention provides: an optical laminate in which a first polarizing plate and a second polarizing plate each including a polarizer are layered such that the absorption axis directions of the polarizers are substantially parallel, and a print layer is provided along the outer peripheral section of the surface of the first polarizing plate on the side where the second polarizing plate is disposed; and an image display device comprising a display element and the optical laminate in this order toward the viewing side.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to an optical laminate and an image display device. [Background technology]

[0002] In recent years, automobiles have been equipped with displays for various purposes, including instrument displays, car navigation systems, rearview monitors, and audio-visual systems. In such in-vehicle displays, a colored area is generally provided along the outer edge of the display screen to harmonize its appearance with the display's frame, instrument panel, console, and other surrounding components, and to conceal wiring, terminals, etc. This creates a distinction between the display area and the non-display area. Similarly, in general-purpose or professional tablet devices, a colored area is often provided along the outer edge of the display screen.

[0003] In image display devices with a colored area along the outer edge of the display screen, the difference in appearance between the display area (black screen) and the non-display area (colored area) can be noticeable when the display is not in use (power off), and improvements are needed from an aesthetic standpoint.

[0004] In relation to the above request, Patent Document 1 proposes a display device that reduces the color difference between the display area and the non-display area when the display is not in use, but there is a need for further improvement. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2020-192708 [Overview of the project] [Problems that the invention aims to solve]

[0006] The present invention was made to solve the above problems, and its main objective is to provide an image display device in which a colored area is provided along the outer edge of the display screen, and in which the difference in appearance between the display area and the non-display area when the display area is not displayed is difficult to perceive. [Means for solving the problem]

[0007] According to one aspect of the present invention, an optical laminate is provided in which a first polarizing plate and a second polarizing plate, each containing a polarizer, are laminated such that the absorption axis directions of their respective polarizers are substantially parallel, and a printed layer is provided along the outer periphery of the side of the first polarizing plate on which the second polarizing plate is arranged. In one embodiment, the total light transmittance of the optical laminate exceeds 35.0%. In one embodiment, the thickness of the printed layer is 3 μm to 30 μm. In one embodiment, the first polarizing plate and the second polarizing plate are bonded together via an adhesive layer. In one embodiment, a surface substrate layer is laminated on the side of the first polarizing plate opposite to the side on which the second polarizing plate is positioned. In one embodiment, a surface substrate layer is laminated on the side of the second polarizing plate opposite to the side on which the first polarizing plate is located. According to another aspect of the present invention, an image display device is provided, comprising a display element and the optical laminate in this order facing the viewing side. In one embodiment, when the printed layer is not visible, the SCI-based L*a*b* color difference (CIE 1976) between the portion with the printed layer and the portion without the printed layer, as viewed from the viewing side, is less than 1.5. In one embodiment, the reflectance of the portion where the printed layer is provided, as viewed from the viewing side when it is not visible, is 2.5% or less, according to the SCI method. In one embodiment, the display element includes a liquid crystal cell, an organic electronic element, or an inorganic electronic element. In one embodiment, the display element further includes a touch panel. [Effects of the Invention]

[0008] An image display device according to an embodiment of the present invention has a configuration in which two polarizers are coaxially stacked on the viewing side of the display element, with a printed layer placed between them. By adopting such a configuration, it is possible to make it difficult to perceive the difference in appearance between the display area and the non-display area when the display area is not visible, without significantly reducing the brightness of the display area. [Brief explanation of the drawing]

[0009] [Figure 1A] (a) is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention, and (b) is a schematic top view of the optical laminate shown in (a). [Figure 1B] This is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. [Figure 1C] This is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. [Figure 2A] This is a schematic cross-sectional view of an image display device according to one embodiment of the present invention. [Figure 2B] This is a schematic cross-sectional view of an image display device according to one embodiment of the present invention. [Figure 2C] This is a schematic cross-sectional view of an image display device according to one embodiment of the present invention. [Modes for carrying out the invention]

[0010] Preferred embodiments of the present invention will be described below, but the present invention is not limited to these embodiments. In this specification, "~" representing a numerical range includes its upper and lower limits.

[0011] A. Optical laminate An optical laminate according to an embodiment of the present invention has a configuration in which a first polarizing plate and a second polarizing plate each including a polarizer are laminated such that absorption axis directions of the respective polarizers are substantially parallel to each other, and a printed layer is provided along an outer peripheral portion of a surface of the first polarizing plate on the side where the second polarizing plate is disposed. The optical laminate is preferably used for manufacturing an image display device, and at this time, is disposed on the viewing side of a display element such as an organic electroluminescent (EL) element, an inorganic EL element, or a liquid crystal cell. By laminating two polarizers on the viewing side of the display element with their absorption axis directions aligned, and disposing a printed layer between the polarizers, it is possible to reduce the color difference and reflectance between the display region and the non-display region on the display screen during non-display, while suppressing a decrease in the luminance of the image display device, and as a result, the effect of making the boundary therebetween less likely to be recognized can be obtained. In the following description, making the difference in appearance between the display region and the non-display region less likely to be recognized (making it less noticeable) may be referred to as "seamlessness between the display region and the non-display region".

[0012] A-1. Overall configuration of optical laminate Figure 1A is a schematic cross-sectional view (a) and a schematic top view (b) of an optical laminate according to one embodiment of the present invention. In the optical laminate 100a shown in Figure 1A, a first polarizer plate 10 including a first polarizer 12 and a second polarizer plate 20 including a second polarizer 22 are laminated such that the absorption axis directions of the polarizers 12 and 22 are substantially parallel to each other. Furthermore, a printed layer 30 is provided along the outer periphery of the surface of the first polarizer plate 10 on the side where the second polarizer plate 20 is located. As shown in Figure 1(b), the printed layer 30 is provided in a frame shape along the outer periphery of the main surface of the first polarizer plate 10 on the side of the second polarizer plate 20. When the optical laminate 100a is placed on a display element to constitute an image display device, the area where the printed layer 30 is not provided (in other words, the area surrounded by the printed layer 30) becomes the display area A, and the area where the printed layer 30 is provided becomes the non-display area B. In the illustrated example, the first polarizing plate 10 and the second polarizing plate 20 are bonded together via an adhesive layer 40. However, as long as the effects of the present invention are obtained, they may be simply laminated without an adhesive layer such as an adhesive layer or bonding layer. Furthermore, in this specification, "substantially parallel" includes an angle between the two directions in the range of 0°±10°, preferably in the range of 0°±5°, and more preferably in the range of 0°±3°.

[0013] Figures 1B and 1C are schematic cross-sectional views of an optical laminate according to one embodiment of the present invention. In the optical laminate 100b shown in Figure 1B, a surface substrate layer 50 is laminated on the side of the first polarizing plate 10 opposite to the side where the second polarizing plate 20 is located. The surface substrate layer 50 is a layer that can function as the front panel of an image display device, and therefore, the optical laminate 100b can be positioned on the viewing side of a display element such that the first polarizing plate 10, which is a polarizing plate with a printed layer, is on the viewing side of the second polarizing plate 20.

[0014] In the optical laminate 100c shown in Figure 1C, a surface base material layer 50 is laminated on the side of the second polarizing plate 20 opposite to the side on which the first polarizing plate 10 is disposed. As described above, the surface base material layer 50 is a layer that can function as a front plate of an image display device, and thus the optical laminate 100c can be disposed on the viewing side of a display element such that the second polarizing plate 20 is located on the viewing side relative to the first polarizing plate 10 which is a polarizing plate with a printed layer.

[0015] Although not illustrated, the optical laminate may further include a pressure-sensitive adhesive layer for bonding to an adjacent member such as a display element. For example, a pressure-sensitive adhesive layer may be provided on one or both surfaces of the optical laminate 100a, on the surface of the optical laminate 100b on the second polarizing plate 20 side, or on the surface of the optical laminate 100c on the first polarizing plate 10 side. These pressure-sensitive adhesive layers disposed in the outermost layer of the optical laminate may be protected by a release liner until put to use.

[0016] The optical laminate according to the embodiment of the present invention is not limited to the configuration in the illustrated example. For example, the respective embodiments can be appropriately combined. In addition, the optical laminate may further include any appropriate component according to the purpose. Examples of such a component include a retardation layer, a surface protective film, and the like. The respective components can be laminated via any appropriate adhesive layer (pressure-sensitive adhesive layer, adhesive layer, etc.) as needed.

[0017] The total light transmittance of the display region of the optical laminate is, for example, more than 35.0%, preferably 39.0% to 42.5%, and more preferably 42.5% to 45%.

[0018] The reflectance (SCI method) of the non-display area of ​​the optical laminate is, for example, 10% or less or less than 10%, preferably 1.0% to 10%, more preferably 1.0% to 5.0%. The reflectance (SCI method) of the display area is, for example, 10% or less or less than 10%, preferably 1.0% to 10%, more preferably 1.0% to 5.0%. If the optical laminate includes a surface substrate layer (for example, a surface substrate layer having an anti-reflective layer), the reflectance (SCI method) of the non-display area of ​​the optical laminate may be, for example, less than 2.5%, preferably 0.5% to 2.0%, more preferably 0.5% to 1.0%. The reflectance (SCI method) of the display area may be, for example, less than 2.5%, preferably 0.5% to 2.0%, more preferably 0.5% to 1.0%.

[0019] The reflectance of the non-display area of ​​the optical laminate (SCE method) is, for example, less than 1.5%, preferably 0.1% to 1.0%, and more preferably 0.1% to 0.5%. The reflectance of the display area (SCE method) is, for example, less than 1.5%, preferably 0.1% to 1.0%, and more preferably 0.1% to 0.5%.

[0020] The thickness of the optical laminate is, for example, 100 μm to 4000 μm, preferably 200 μm to 2000 μm.

[0021] A-2. First polarizing plate and second polarizing plate The first polarizer and the second polarizer each include a polarizer, and typically further include a protective layer provided on one or both sides of the polarizer. The first polarizer and the second polarizer may have the same configuration or different configurations. With respect to the polarizer and protective layer that the first polarizer and the second polarizer may include, the following description applies equally unless otherwise specified. The surface substrate layer that can function as a front plate may be larger in size than the other components, but if the first polarizer is positioned on the viewing side than the second polarizer, the first polarizer may be formed to be the same size as the surface substrate layer.

[0022] A-2-1. Polarizer Polarizers are typically composed of a polyvinyl alcohol-based resin film containing a dichroic substance (e.g., iodine). Polarizers may be made of a single layer of resin film, or they may be made using a laminate of two or more layers.

[0023] Specific examples of polarizers composed of a single layer of resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films, which have been subjected to dyeing and stretching treatments with dichroic substances such as iodine or dichroic dyes, as well as polyene-based oriented films such as dehydrated PVA or dehydrochlorinated polyvinyl chloride. Preferably, polarizers obtained by dyeing a PVA film with iodine and uniaxially stretching are used because they have excellent optical properties.

[0024] The above-mentioned iodine dyeing is carried out, for example, by immersing the PVA film in an iodine aqueous solution. The stretching ratio for the above-mentioned uniaxial stretching is preferably 3 to 7 times. Stretching may be performed after the dyeing treatment, or during the dyeing process. Alternatively, dyeing may be performed after stretching. If necessary, the PVA film may be subjected to swelling, crosslinking, washing, drying, etc. For example, immersing the PVA film in water and washing it before dyeing can not only wash away dirt and blocking agents from the surface of the PVA film, but also swell the PVA film to prevent uneven dyeing.

[0025] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced, for example, by applying a PVA-based resin solution to a resin substrate, drying it to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; or by stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, stretching may, if necessary, further include air-stretching the laminate at a high temperature (e.g., 95°C or higher) before stretching in the aqueous boric acid solution. The resulting resin substrate / polarizer laminate may be used as is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the resin substrate / polarizer laminate, and any appropriate protective layer may be laminated onto the peeled surface according to the purpose. Details of such a polarizer manufacturing method are described, for example, in Japanese Patent Application Publication No. 2012-73580. The entire description of that publication is incorporated herein by reference.

[0026] The thickness of the polarizer is, for example, 30 μm or less, preferably 15 μm or less, more preferably 1 μm to 12 μm, even more preferably 2 μm to 10 μm, and even more preferably 2 μm to 8 μm.

[0027] The polarizer preferably exhibits absorption dichroism at any wavelength between 380 nm and 780 nm. The transmittance of the polarizer is, for example, 41.0% or more, preferably 43.0% to 46.0%, and more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0028] A-2-2.Protective layer The protective layer is composed of any suitable film that can be used as a protective layer for the polarizer. Specific examples of materials that make up the main component of the film include cellulosic resins such as triacetylcellulose (TAC), and transparent resins such as polyester, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, polynorbornene, polyolefin, (meth)acrylic, and acetate. Thermosetting resins or UV-curing resins such as (meth)acrylic, urethane, (meth)acrylic urethane, epoxy, and silicone can also be used. In addition, glassy polymers such as siloxane polymers can also be used. Polymer films described in Japanese Patent Application Publication No. 2001-343529 (WO01 / 37007) can also be used. As materials for this film, for example, a resin composition containing a thermoplastic resin having substituted or unsubstituted imide groups in its side chains, and a thermoplastic resin having substituted or unsubstituted phenyl groups and nitrile groups in its side chains can be used. Examples include a resin composition having an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extruded product of the above resin composition.

[0029] When a polarizing plate is applied to an image display device, the thickness of the protective layer (outer protective layer) positioned on the opposite side of the display element is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and even more preferably 10 μm to 60 μm. If a surface treatment is applied, the thickness of the outer protective layer includes the thickness of the surface treatment layer.

[0030] When a polarizing plate is applied to an image display device, the thickness of the protective layer (inner protective layer) placed on the display element side is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and even more preferably 10 μm to 60 μm.

[0031] In one embodiment, the inner protective layer is optically isotropic. In this specification, "optically isotropic" means that the in-plane phase difference Re(550) of the phase difference layer is 0 nm to 10 nm, and the phase difference Rth(550) in the thickness direction is -10 nm to +10 nm. In another embodiment, the inner protective layer (typically the inner protective layer of a polarizer placed on the display element side) is optically anisotropic and is a phase difference layer having any appropriate phase difference value. The in-plane phase difference Re(550) of the phase difference layer is, for example, 120 nm to 160 nm, preferably 135 nm to 155 nm. In this case, the inner protective layer is a λ / 4 plate, and can be made into a circular polarizer by arranging it so that the angle between its slow axis direction and the absorption axis direction of the polarizer is, for example, 45° ± 10°, preferably 45° ± 5°, more preferably 45°. Here, "Re(550)" is the in-plane phase difference measured with light of a wavelength of 550 nm at 23°C, and is calculated by the formula: Re=(nx-ny)×d. Also, "Rth(550)" is the phase difference in the thickness direction measured with light of a wavelength of 550 nm at 23°C, and is calculated by the formula: Rth(λ)=(nx-nz)×d. Here, "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow phase axis direction), "ny" is the refractive index in the direction perpendicular to the slow phase axis in the plane (i.e., the fast phase axis direction), "nz" is the refractive index in the thickness direction, and "d" is the thickness of the layer (film) (nm).

[0032] A-3.Printing layer The printed layer is a colored layer that is colored by printing according to the application and desired design. The printed layer may be a design layer with a predetermined design, or it may be a solid colored layer. The printed layer is preferably a solid colored layer, more preferably a dark colored layer such as black, blue, navy blue, purple, or brown (for example, L* in the SCI L*a*b* color space is 50 or less, a* is in the range of +10 to -10, and b* is in the range of +10 to -10), and even more preferably a black colored layer (for example, L* in the SCI L*a*b* color space is 20 or less, a* is in the range of +5 to -5, and b* is in the range of +5 to -5). By making the printed layer a black colored layer, wiring, terminals, backlights, and other components can be suitably concealed in the non-display area.

[0033] The printed layer can be formed in any suitable pattern depending on the purpose. Typically, the printed layer is formed in a frame shape along the outer periphery of the main surface of the polarizing plate, for example, at a position corresponding to the bezel. With such a configuration, the non-display area can be concealed without using a bezel.

[0034] The printed layer can be formed using a printing layer-forming composition and any suitable printing method. Specific examples of printing methods include gravure printing, offset printing, screen printing, and transfer printing from transfer sheets.

[0035] A composition for forming a printing layer typically comprises a binder, a colorant, a solvent, and any suitable additives that may be used as needed. Examples of binders include chlorinated polyolefins (e.g., chlorinated polyethylene, chlorinated polypropylene), polyester resins, urethane resins, acrylic resins, vinyl acetate resins, vinyl chloride-vinyl acetate copolymers, and cellulose resins. The binder resin may be used alone or in combination of two or more. In one embodiment, the binder resin is a thermopolymerizable resin. Since thermopolymerizable resins require less material than photopolymerizable resins, the amount of colorant used (colorant content in the colored layer) can be increased. As a result, especially when forming a black colored layer, a colored layer with very low total light transmittance and excellent opacity can be formed. In one embodiment, the binder resin is a (meth)acrylic resin, preferably a (meth)acrylic resin containing a polyfunctional monomer (e.g., pentaerythritol tri(meth)acrylate) as a copolymer component. By using a (meth)acrylic resin containing polyfunctional monomers as copolymer components, a printed layer with an appropriate elastic modulus can be formed. In addition, a step is formed due to the thickness of the printed layer, and this step can effectively function to prevent blocking.

[0036] As a colorant, any suitable colorant can be used depending on the purpose and desired color. The colorant may be a pigment or a dye, and is preferably a pigment. Specific examples of colorants include inorganic pigments such as titanium white, zinc oxide, carbon black, iron black, red iron oxide, chrome vermilion, ultramarine, cobalt blue, lead yellow, and titanium yellow; organic pigments or dyes such as phthalocyanine blue, induthlene blue, isoindolinone yellow, benzidine yellow, quinacridone red, polyazo red, perylene red, and aniline black; metallic pigments consisting of flaky foil pieces such as aluminum and brass; and pearlescent pigments (pearl pigments) consisting of flaky foil pieces such as titanium dioxide-coated mica and basic lead carbonate. When forming a black colored layer, carbon black, iron black, and aniline black are preferably used. In this case, it is preferable to use colorants in combination, as they can absorb visible light broadly and uniformly, forming a colorless (i.e., completely black) colored layer. For example, in addition to the above colorants, azo compounds and / or quinone compounds may be used. In one embodiment, the colorant comprises carbon black as the main component and other colorants (e.g., azo compounds and / or quinone compounds). With such a configuration, a colored layer that is colorless and has excellent aging stability can be formed. When forming a black colored layer, the colorant may be used in a ratio of preferably 50 to 200 parts by weight per 100 parts by weight of the binder resin. In this case, the carbon black content in the colorant is preferably 80% to 100%. By using the colorant (especially carbon black) in such a ratio, a colored layer with very low total light transmittance and excellent aging stability can be formed.

[0037] The total light transmittance of the printed layer is preferably 0.01% or less, and more preferably 0.008% or less. When the total light transmittance is within this range, the non-display areas of the image display device can be effectively concealed.

[0038] The thickness of the printed layer is, for example, 3 μm to 30 μm, preferably 5 μm to 20 μm, and more preferably 10 μm to 15 μm. If the thickness of the printed layer is within this range, a seamless effect between the display area and the non-display area can be suitably obtained.

[0039] A-4.Adhesive layer Any suitable adhesive composition applicable to optical applications can be used as the adhesive composition for forming the adhesive layer used for bonding the first polarizing plate and the second polarizing plate, and for bonding any other components. The total light transmittance of the adhesive layer is preferably 85% or more, more preferably 88% or more. The haze of the adhesive layer is preferably 1.0% or less, more preferably 0.8% or less.

[0040] Any suitable adhesive composition can be used as the above-mentioned adhesive composition. Examples include rubber-based, acrylic-based, silicone-based, urethane-based, vinyl alkyl ether-based, polyvinyl alcohol-based, polyvinylpyrrolidone-based, polyacrylamide-based, and cellulose-based adhesive compositions. Among these, acrylic-based adhesive compositions are preferred because they offer excellent optical transparency, as well as superior adhesive properties, weather resistance, and heat resistance.

[0041] The above acrylic adhesive composition contains a partially polymerized monomer component containing alkyl (meth)acrylate and / or a (meth)acrylic polymer obtained from said monomer component as a base polymer.

[0042] Examples of the alkyl (meth)acrylates mentioned above include those having a linear or branched alkyl group with 1 to 24 carbon atoms at the ester end. Alkyl (meth)acrylates can be used individually or in combination of two or more. In this specification, "(meth)acrylate" means acrylate and / or methacrylate.

[0043] Examples of the alkyl (meth)acrylates mentioned above include branched alkyl (meth)acrylates having 4 to 9 carbon atoms. Such alkyl (meth)acrylates are preferred because they offer a good balance of adhesive properties. Specifically, examples include n-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and isononyl (meth)acrylate, which can be used individually or in combination of two or more.

[0044] The alkyl (meth)acrylate having an alkyl group with 1 to 24 carbon atoms at its ester terminus is preferably present in an amount of 40% by weight or more, more preferably 50% by weight or more, and even more preferably 60% by weight or more, relative to the total amount of monofunctional monomer components forming the (meth)acrylic polymer.

[0045] The above monomer component may include, as a monofunctional monomer component, copolymer monomers other than the alkyl (meth)acrylate (for example, carboxyl group-containing monomers, hydroxyl group-containing monomers, amide group-containing monomers, aromatic ring-containing (meth)acrylates, etc.). The copolymer monomer can be used as the remainder of the alkyl (meth)acrylate in the monomer component.

[0046] The copolymer monomer and its amount used may be those described in paragraphs 0029 to 0042 of Japanese Patent Publication No. 2016-157077 or those described in paragraphs 0022 to 0036 of Japanese Patent Publication No. 2016-190996.

[0047] In addition to monofunctional monomers, the monomer components forming the above-mentioned (meth)acrylic polymer may also contain polyfunctional monomers as needed to adjust the cohesive force of the adhesive.

[0048] Polyfunctional monomers are monomers having at least two polymerizable functional groups having unsaturated double bonds, such as (meth)acryloyl groups or vinyl groups, for example, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate Examples include ester compounds of polyhydric alcohols such as methylcellulose, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate with (meth)acrylic acid; allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, epoxyacrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. Among these, trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate can be preferably used. Polyfunctional monomers can be used individually or in combination of two or more.

[0049] The amount of polyfunctional monomer used varies depending on its molecular weight and number of functional groups, but it is preferably used in amounts of 3 parts by weight or less, more preferably 2 parts by weight or less, and even more preferably 1 part by weight or less, per 100 parts by weight of monofunctional monomers. While there is no particular lower limit, it is preferably 0 parts by weight or more, and more preferably 0.001 parts by weight or more. By using polyfunctional monomers within the above range, the adhesive strength can be improved.

[0050] The weight-average molecular weight of the above (meth)acrylic polymer is, for example, 1 million to 2.5 million, preferably 1.2 million to 2 million. Furthermore, the molecular weight distribution (weight-average molecular weight (Mw) / number-average molecular weight (Mn)) is preferably 1.8 or more and 10 or less, more preferably 1.8 to 7, and even more preferably 1.8 to 5. The weight-average molecular weight and molecular weight distribution (Mw / Mn) are determined by GPC (gel permeation chromatography) and calculated using polystyrene equivalents.

[0051] The above-mentioned (meth)acrylic polymer can be manufactured by any suitable method. For example, solution polymerization, radiation polymerization such as ultraviolet (UV) polymerization, bulk polymerization, emulsion polymerization, and other radical polymerization methods can be appropriately selected. Various known azo-based and peroxide-based radical polymerization initiators can be used. The reaction temperature is usually around 50-80°C, and the reaction time is 1-8 hours. Among the above manufacturing methods, solution polymerization is preferred, and ethyl acetate, toluene, etc., are generally used as the solvent for the (meth)acrylic polymer. The solution concentration is usually around 20-80% by weight. The resulting (meth)acrylic polymer may be a random copolymer, block copolymer, graft copolymer, etc.

[0052] The above adhesive composition may contain a crosslinking agent. Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, silicone-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl ether-modified melamine-based crosslinking agents, metal chelate-based crosslinking agents, and peroxides. The crosslinking agent may be used individually or in combination of two or more. Among these, isocyanate-based crosslinking agents are preferred.

[0053] The mixing ratio of (meth)acrylic polymer to crosslinking agent is usually preferably about 0.001 to 20 parts by weight of crosslinking agent (solids) per 100 parts by weight of (meth)acrylic polymer (solids), and more preferably about 0.01 to 15 parts by weight of crosslinking agent (solids).

[0054] The above adhesive composition may further contain various additives as needed, such as ultraviolet absorbers; tackifiers such as rosin derivative resins, polyterpene resins, petroleum resins, and oil-soluble phenolic resins; plasticizers; fillers such as hollow glass balloons; pigments; colorants; antioxidants; anti-aging agents; and silane coupling agents. The amount of additives used can be appropriately set depending on the purpose. For example, the amount of silane coupling agent used is preferably 1 part by weight or less, more preferably 0.01 to 1 part by weight, and even more preferably 0.02 to 0.6 parts by weight, per 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer.

[0055] The above adhesive composition is preferably adjusted to a viscosity suitable for application. Viscosity adjustment can be achieved by adding thickening polymers, polyfunctional monomers, etc., or by partially polymerizing the monomer components in the adhesive composition. This partial polymerization may be performed before or after the addition of thickening polymers, polyfunctional monomers, etc. Since the viscosity of the adhesive composition can change depending on the composition of the monomer components, the type and amount of additives, etc., it is difficult to uniquely determine a preferred polymerization rate for partial polymerization. However, the polymerization rate may be, for example, around 20% or less, preferably 3% to 20%, and more preferably around 5% to 15%. If the polymerization rate in partial polymerization exceeds 20%, the viscosity becomes too high, making application to the substrate difficult.

[0056] The adhesive layer is formed by applying the above-mentioned adhesive composition to various substrates and, if necessary, drying, irradiation, etc. When the adhesive layer is formed on a release film, the adhesive layer can be transferred from the release film onto a desired component for use.

[0057] The thickness of the adhesive layer used to bond the first polarizing plate and the second polarizing plate (thickness in the display area) is, for example, 50 μm to 1000 μm, preferably 200 μm to 750 μm, and more preferably 250 μm to 500 μm. The thickness of the adhesive layer used to bond any other components may be, for example, 1 μm to 300 μm, preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm.

[0058] A-5.Surface base material layer The surface substrate layer can function as the front panel of an image display device. Therefore, preferably, the surface substrate layer is positioned as the outermost surface when the optical laminate is placed on the viewing side of the display element. The surface substrate layer includes a base film and may further include functional layers such as an anti-reflective layer, an anti-fouling layer, or a hard coat layer, as needed. The surface substrate layer preferably includes an anti-reflective layer. Examples of anti-reflective layers include a thin-layer type that prevents reflection by utilizing the cancellation effect of reflected light due to the interference of light, as disclosed in Japanese Patent Application Publication No. 2005-248173, and a surface structure type that exhibits low reflectivity by providing a microstructure on the surface, as disclosed in Japanese Patent Application Publication No. 2011-2759. One or more functional layers can be used in combination. The functional layers may be laminated onto the base film via an adhesive layer (e.g., a tack layer, an adhesive layer) while formed on a support film as needed, or they may be formed directly on the base film without an adhesive layer.

[0059] As the base film, a glass film or a resin film can be used.

[0060] Examples of glass materials that make up the glass film include soda-lime glass, borate glass, aluminosilicate glass, and quartz glass, according to their composition. Examples of glass materials that make up the glass film include alkali-free glass and low-alkali glass, according to their alkali content. The thickness of the glass film is preferably 100 μm to 2000 μm, and more preferably 200 μm to 1000 μm.

[0061] Examples of resins that make up the resin film include polyethylene terephthalate resins, polyethylene naphthalate resins, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyamide-imide resins, polyolefin resins, (meth)acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, and polyphenylene sulfide resins. Among these, polyamide resins, polyimide resins, polyamide-imide resins, polyethylene naphthalate resins, and polycarbonate resins are preferred, with polyimide resins being more preferred. These resins may be used individually or in combination of two or more. The thickness of the resin film is preferably 100 μm to 2000 μm, and more preferably 200 μm to 1000 μm.

[0062] A-6. Peel-off liner Examples of release liners include plastic films (e.g., polyethylene terephthalate (PET), polyethylene, polypropylene), nonwoven fabrics, or paper, whose surfaces are coated with release agents such as silicone-based release agents, fluorine-based release agents, or long-chain alkyl acrylate-based release agents. The thickness of the release liner is, for example, 10 μm to 100 μm.

[0063] A-7. Other Components The surface protection film comprises a substrate and an adhesive layer provided on one side of the substrate. The surface protection film is provided to prevent scratches and stains on the surface of the optical laminate (e.g., the surface of the surface substrate layer) and is usually peeled off before use.

[0064] As the phase difference layer, a phase difference layer functioning as a λ / 4 plate is preferably used. The phase difference layer functioning as a λ / 4 plate has an in-plane phase difference Re(550) of, for example, 120 nm to 160 nm, preferably 135 nm to 155 nm. Furthermore, the phase difference layer functioning as a λ / 4 plate may be arranged so that its slow axis direction forms an angle of, for example, 45° ± 10°, preferably 45° ± 5°, and more preferably 45° with respect to the absorption axis direction of the polarizer. With this configuration, excellent circular polarization function can be achieved, and when used in combination with, for example, an organic EL element, it can exhibit an anti-reflective function.

[0065] A phase difference layer functioning as a λ / 2 plate may be placed between the polarizer and the phase difference layer functioning as a λ / 4 plate. In this case, the angle between the absorption axis of the polarizer and the slow axis of the λ / 4 plate is preferably 65° to 85°, more preferably 72° to 78°, and even more preferably about 75°. The angle between the absorption axis of the polarizer and the slow axis of the λ / 2 plate is preferably 10° to 20°, more preferably 13° to 17°, and even more preferably about 15°. The phase difference layer functioning as a λ / 2 plate has an in-plane phase difference Re(550) of, for example, 210nm to 280nm, preferably 230nm to 240nm.

[0066] The phase difference layer is typically located on the display element side of the polarizing plate, and its axial relationship with the polarizing plate is as described above.

[0067] B. Image display device An image display device according to an embodiment of the present invention comprises a display element and an optical laminate described in Section A, in this order facing the viewing side. In one embodiment, the image display device comprises a display element, a second polarizer, a printed layer, and a first polarizer, in this order facing the viewing side, wherein the printed layer is provided along the outer periphery of the surface of the first polarizer on which the second polarizer is located, and the first polarizer and the second polarizer are arranged such that the absorption axis directions of their respective polarizers are substantially parallel to each other. In another embodiment, the image display device comprises a display element, a first polarizer, a printed layer, and a second polarizer, in this order facing the viewing side, wherein the printed layer is provided along the outer periphery of the surface of the first polarizer on which the second polarizer is located, and the first polarizer and the second polarizer are arranged such that the absorption axis directions of their respective polarizers are substantially parallel to each other. Image display devices with this configuration offer superior design appeal because the difference in appearance between the display area (the area without a printed layer in a planar view) and the non-display area (the area with a printed layer in a planar view) is small when the display is not showing any content. Furthermore, the high transmittance of the optical laminate itself suppresses a decrease in brightness.

[0068] In the display area of ​​the display screen when it is not visible, the SCI method L*a*b* color space is, for example, L* preferably 15 or less, more preferably 10 or less, a* preferably -10 to +10, more preferably -5 to +5, and b* preferably -10 to +10, more preferably -5 to +5. Also, in the display area of ​​the display screen when it is not visible, the SCE method L*a*b* color space is, for example, L* preferably 10 or less, more preferably 5 or less, a* preferably -10 to +10, more preferably -5 to +5, and b* preferably -10 to +10, more preferably -5 to +5.

[0069] The L*a*b* color difference (CIE 1976) ΔE*ab of the SCI method between the displayed area and the hidden area of ​​the display screen when the area is hidden is preferably less than 1.5, more preferably 1.4 or less, even more preferably 1.3 or less, and still more preferably 1.2 or less. Similarly, the L*a*b* color difference (CIE 1976) ΔE*ab of the SCE method is preferably less than 4.0, more preferably 2.5 or less, and even more preferably 1.5 or less. If ΔE*ab is within the above range, the difference in appearance between the displayed area and the hidden area of ​​the display screen when the area is hidden is difficult to perceive. The L*a*b* color difference (CIE 1976) ΔE*ab is calculated using the following formula (wherein L* represents lightness, a* represents chromaticity a*, and b* represents chromaticity b*). ΔE*ab = [(ΔL*)] 2 +(Δa*) 2 +(Δb*) 2 ] 1 / 2

[0070] The reflectance of the SCI method in the display area of ​​the display screen when it is not visible is preferably less than 2.5%, more preferably 2.0% or less, and even more preferably 1.5% or less. The reflectance in the non-visible area is preferably 2.5% or less, more preferably 2.0% or less, and even more preferably 1.5% or less. The difference in reflectance between the two areas is preferably 0.3% or less, and more preferably 0.15% or less.

[0071] The reflectance of the SCE method in the display area of ​​the display screen when it is not showing is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.3% or less. The reflectance in the non-showing area is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.3% or less. The difference in reflectance between the two areas is preferably 0.3% or less, and even more preferably 0.15% or less.

[0072] Examples of the display elements mentioned above include liquid crystal cells, organic EL elements, and inorganic EL elements. The display elements may also further include touch panels. Since these display elements are well known to those skilled in the art, a detailed explanation will be omitted.

[0073] Figure 2A is a schematic cross-sectional view of an image display device (liquid crystal display device) that includes a liquid crystal cell as a display element. The image display device 200a comprises a backlight unit 110, a back polarizing plate 120, a liquid crystal cell 130, and an optical laminate 100 in this order facing the viewing side. Preferably, the optical laminate 100 has an adhesive layer (not shown) on the outside of the second polarizing plate 20, and is bonded to the liquid crystal cell 130 via this adhesive layer. Typically, the optical laminate 100 is arranged such that the absorption axis direction of the second polarizing plate 20 (polarizer 22) and the absorption axis direction of the back polarizing plate 120 are substantially orthogonal (for example, 90°±5°, preferably 90°±3°), and the second polarizing plate 20, the liquid crystal cell 130, and the back polarizing plate 120 constitute a liquid crystal panel.

[0074] Figure 2B is a schematic cross-sectional view of an image display device (liquid crystal display device) that includes a liquid crystal cell and a touch panel as display elements. The image display device 200b comprises a backlight unit 110, a back polarizing plate 120, a liquid crystal cell 130, a touch panel 140, and an optical laminate 100 in this order facing the viewing side. Preferably, the optical laminate 100 has an adhesive layer (not shown) on the outside of the second polarizing plate 20, and is bonded to the touch panel 140 via this adhesive layer. Furthermore, the optical laminate 100 is arranged such that the absorption axis direction of the second polarizing plate 20 (polarizer 22) and the absorption axis direction of the back polarizing plate 120 are substantially orthogonal. In the illustrated example, the touch panel has an on-cell structure, but it may also have an in-cell structure.

[0075] Figure 2C is a schematic cross-sectional view of an image display device (organic EL display device) that includes an organic EL element as a display element. The image display device 200c comprises an organic EL element 150 and an optical laminate 100 in this order facing the viewing side. The optical laminate 100 has a phase difference layer 60 which is a λ / 4 plate on the back side of the second polarizing plate 20, and the phase difference layer 60 is arranged such that the angle between its absorption axis direction and the absorption axis direction of the polarizer 22 is 45°. The optical laminate 100 is preferably bonded to the organic EL element 150 via an adhesive layer (not shown) provided on the outside of the phase difference layer 60.

[0076] In the illustrated example above, the first polarizer is positioned on the viewing side of the second polarizer; however, the second polarizer may be positioned on the viewing side of the first polarizer. Needless to say, in either configuration, the surface substrate layer is positioned on the viewing side. [Examples]

[0077] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The measurement methods for each characteristic are as follows. (1) Thickness Measurements were taken using a digital gauge (manufactured by Ozaki Seisakusho Co., Ltd., product name "PEACOCK"). (2) L*a*b* color space, color difference ΔE*ab and reflectance The spectral reflectance was measured using a spectrophotometer (CM-2600d, manufactured by Konica Minolta) under the following measurement conditions, and L*a*b* was determined. (Measurement conditions) Type of light-receiving optical system: SCI (including specular reflection) or SCE (excluding specular reflection) Measurement wavelength range: 360nm-740nm Light source: D65 Measurement diameter MAV: φ8mm Furthermore, the color difference (ΔE*ab) was calculated using the following formula. ΔE*ab = [(ΔL*)] 2 +(Δa*) 2 +(Δb*) 2 ] 1 / 2 (3) Single transmittance and degree of polarization of polarizer A polarizing plate (protective layer / polarizer / protective layer) was measured using an ultraviolet-visible-near-infrared spectrophotometer (V-7100 manufactured by JASCO Corporation), and the obtained single transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc were respectively defined as Ts, Tp and Tc of the polarizer. These Ts, Tp and Tc are Y values measured with a 2-degree field of view (C light source) in accordance with JIS Z8701 and subjected to luminosity correction. From the obtained Tp and Tc, the degree of polarization was determined using the following formula. Degree of polarization (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 (4) Total light transmittance A transparent acrylic pressure-sensitive adhesive layer (manufactured by Nitto Denko Corporation, thickness 20 μm, total light transmittance 88% or more, haze 0.8% or less) was provided on the polarizing plate side of the optical laminates obtained in Examples and Comparative Examples, and the resultant product laminated on a 1 mm thick glass film (manufactured by Matsunami Glass Ind., Ltd., product name "Soda Lime Glass") via the acrylic pressure-sensitive adhesive layer was used as a measurement sample. The transmittance at a wavelength of 380 nm to 780 nm measured using an ultraviolet-visible-near-infrared spectrophotometer (V-7100 manufactured by JASCO Corporation) was defined as the total light transmittance. The total light transmittance is a Y value measured with a 2-degree field of view (C light source) in accordance with JIS Z8701 and subjected to luminosity correction. (5) Haze Measurement was performed by the method specified in JIS 7136 using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., trade name "HN-150").

[0078] [Production Example 1: Pressure-sensitive adhesive layer A containing no coloring material] A monomer mixture consisting of 60 parts by weight of butyl acrylate (BA), 6 parts by weight of cyclohexyl acrylate (CHA), 26 parts by weight of 4-hydroxybutyl acrylate (4HBA), and 8 parts by weight of hydroxyethyl acrylate (HEA) was mixed with 0.09 parts by weight of 2,2-dimethoxy-1,2-diphenyl-1-one (trade name "Irgacure 651", manufactured by BASF Japan) and 0.09 parts by weight of 1-hydroxy-cyclohexyl-phenyl-ketone (trade name "Irgacure 184", manufactured by BASF Japan) in a four-necked flask. Partial photopolymerization was then carried out by exposure to ultraviolet light under a nitrogen atmosphere to obtain a partially polymerized product (monomer syrup) with a polymerization rate of approximately 10%. To 100 parts by weight of this partially polymerized product, 0.12 parts by weight of dipentaerythritol hexaacrylate (KAYARAD DPHA, manufactured by Nippon Kayaku Co., Ltd.) as a polyfunctional polymerizable compound, and 0.3 parts by weight of 3-glycidoxypropyltrimethoxysilane (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) as a silane coupling agent were added and uniformly mixed to prepare an adhesive (adhesive composition). This yielded adhesive composition A.

[0079] Adhesive composition A obtained above was applied to a 38 μm thick release liner R1 (Mitsubishi Plastics, MRF#38) with one side of the polyester film being a release surface. A 38 μm thick release liner R2 (Mitsubishi Plastics, MRE#38) with one side of the polyester film being a release surface was then placed over it to block air, and the adhesive layer A (250 μm thick, total light transmittance 92.0%, haze 0.3%) was formed by curing with ultraviolet light.

[0080] [Manufacturing Example 2: Adhesive layer B containing colorant] An adhesive layer B (thickness 250 μm, total light transmittance 71.0%, haze 1.9%) was formed in the same manner as in Manufacturing Example 1, except that 0.09 parts of 9050 BLACK (manufactured by Tokushiki) were added as a colorant per 100 parts by weight of polymer.

[0081] [Production Example 3: Composition for forming printing layer] A composition for forming a black printing layer was obtained by impregnating Seiko Advance's "HF GV3 RX01" as a coloring agent (black pigment) with a solvent at a concentration of 10% by weight.

[0082] [Manufacturing Example 4: Polarizing Plate] 1. Fabrication of a polarizer A polyvinyl alcohol film with an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol%, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was immersed in a 20°C swelling bath (water bath) for 30 seconds between rolls with different peripheral speed ratios to swell and stretched to 2.2 times its original size in the conveying direction (swelling process). Subsequently, it was immersed in a 30°C dyeing bath (aqueous solution with an iodine concentration of 0.1 wt% and a potassium iodide concentration of 0.9 wt%) for 30 seconds to dye and stretched to 3.3 times its original size in the conveying direction, relative to the original polyvinyl alcohol film (a polyvinyl alcohol film that had not been stretched at all in the conveying direction) (dyeing process). Next, the dyed polyvinyl alcohol film was immersed in a 40°C crosslinking bath (aqueous solution with a boric acid concentration of 3.0 wt% and a potassium iodide concentration of 3.0 wt%) for 28 seconds and stretched to 3.6 times its original size in the conveying direction, relative to the original polyvinyl alcohol film (crosslinking process). Furthermore, the obtained polyvinyl alcohol film was immersed in a 61°C stretching bath (an aqueous solution with a boric acid concentration of 4.0 wt% and a potassium iodide concentration of 5.0 wt%) for 60 seconds to stretch it to 6.0 times its original size in the transport direction (stretching step), and then immersed in a 20°C washing bath (an aqueous solution with a potassium iodide concentration of 2.0 wt%) for 10 seconds (washing step). The washed polyvinyl alcohol film was dried at 40°C for 30 seconds to produce a polarizer. The thickness of the polarizer was 18 μm.

[0083] 2. Fabrication of polarizing plates As an adhesive, an aqueous solution containing polyvinyl alcohol resin containing acetoacetyl groups (average degree of polymerization 1,200, degree of saponification 98.5 mol%, degree of acetoacetylation 5 mol%) and methylolmelamine in a weight ratio of 3:1 was used. Using this adhesive, a 30 μm thick transparent protective film (manufactured by Nippon Shokubai) made of (meth)acrylic resin (modified acrylic polymer having a lactone ring structure) was laminated to one side (display element side) of the polarizer obtained above as a protective layer, and a 49 μm thick transparent protective film made of triacetylcellulose film (manufactured by Fujifilm, product name "TJ40UL") with HC formed on it was laminated to the other side (viewing side) as a protective layer using a roll laminating machine. Subsequently, the polarizer was heated and dried in an oven (temperature 90°C, time 10 minutes) to produce a polarizing plate with transparent protective films laminated to both sides of the polarizer. The transmittance of the obtained polarizer was 41.7%, and the degree of polarization was 99.9%.

[0084] [Manufacturing example 5: Surface base material layer] A glass film with a thickness of 1 mm (manufactured by Matsunami Glass Industry Co., Ltd., product name "Soda-Lime Glass") was bonded to one side with an anti-reflective film (manufactured by Nitto, product name "T-60LA28HCAR6N", thickness 85 μm) having an anti-reflective layer / TAC film configuration, via an adhesive layer A, to obtain a surface substrate layer having the configuration of [glass film / TAC film / anti-reflective layer].

[0085] [Example 1] The polarizers prepared in Manufacturing Example 4 were used as the first and second polarizers. By screen printing, the printing layer-forming composition was applied in a frame shape with a width of 1.5 mm in plan view along the outer circumference of one surface (HC-coated TAC surface) of the first polarizer, and air-dried to form a black printed layer with a thickness of 5 μm. Next, the printing layer-forming composition was applied again on top of the printed layer by screen printing and dried at 50°C for 1 hour to form a black printed layer with a thickness of 5 μm (final thickness of the printed layer: 10 μm). Then, the adhesive layer A was transferred from the release liner to the side of the first polarizer where the printed layer was formed, and the second polarizer was then laminated on top of it. At this time, the first and second polarizers were positioned so that the absorption axes of the polarizers were parallel to each other. Furthermore, the step portion at the boundary between the printed layer and the first polarizer was completely filled with adhesive layer A, and no voids were created. Next, a surface substrate layer was bonded to the side of the first polarizing plate opposite to the side where the second polarizing plate was positioned, via an adhesive layer A, so that the glass film was on the side facing the first polarizing plate. This resulted in an optical laminate having the configuration of [second polarizing plate / adhesive layer A / printed layer / first polarizing plate / surface substrate layer].

[0086] [Comparative Example 1] Using screen printing, the printing layer-forming composition was applied in a frame shape with a width of 1.5 mm in plan view along the outer periphery of the glass film surface of the surface substrate layer, and dried at 80°C for 15 minutes to form a black printing layer with a thickness of 5 μm. Next, the printing layer-forming composition was applied again on top of this printing layer using screen printing, and dried at 120°C for 30 minutes to form a black printing layer with a thickness of 5 μm (final thickness of the formed printing layer: 10 μm). Then, adhesive layer A was transferred from the release liner to the glass film surface on which the printing layer was formed, and the polarizing plate obtained in Manufacturing Example 4 was then laminated on top of it. At this time, the step portion at the boundary between the printing layer and the glass film was completely filled with adhesive layer A, and no voids were created. As a result, an optical laminate having the configuration of [polarizing plate / adhesive layer A / printing layer / surface substrate layer] was obtained.

[0087] [Comparative Example 2] An optical laminate having the configuration of [polarizing plate / adhesive layer B / printed layer / surface substrate layer] was obtained in the same manner as in Comparative Example 1, except that adhesive layer B was used to bond the printed surface substrate layer and the polarizing plate.

[0088] [Comparative Example 3] Using screen printing, the printing layer-forming composition was applied in a frame shape with a width of 1.5 mm in plan view along the outer periphery of one surface (HC-coated TAC surface) of the polarizing plate obtained in Manufacturing Example 4, and air-dried to form a black printed layer with a thickness of 5 μm. Next, the printing layer-forming composition was applied again on top of this printed layer using screen printing, and dried at 50°C for 1 hour to form a black printed layer with a thickness of 5 μm (final thickness of the printed layer: 10 μm). Then, the adhesive layer B was transferred from the release liner to the side of the polarizing plate where the printed layer was formed, and then the surface substrate layer was laminated on top of that so that the glass film was on the polarizing plate side. At this time, the step portion at the boundary between the printed layer and the polarizing plate was completely filled with adhesive layer B, and no voids were created. Thus, an optical laminate having the configuration of [polarizing plate / printed layer / adhesive layer B / surface substrate layer] was obtained.

[0089] [Comparative Example 4] An optical laminate having the configuration of [polarizing plate / printed layer / adhesive layer B / adhesive layer B / surface substrate layer] was obtained in the same manner as in Comparative Example 3, except that two adhesive layers B were laminated (resulting in the use of a colored adhesive layer with a thickness of 500 μm).

[0090] A transparent acrylic adhesive layer (manufactured by Nitto Denko Corporation, 20 μm thick, total light transmittance of 88% or more, haze of 0.8% or less) was provided on the polarizing plate side of the optical laminates of the examples and comparative examples. A black acrylic plate (manufactured by Nitto Resin Industry Co., Ltd., product name "CLAREX") was then bonded to the acrylic adhesive layer to serve as a substitute for the display element when it was not visible, and these were used as evaluation samples. For these evaluation samples, the color difference ΔE*ab between the display area and the non-display area and the reflectance were measured.

[0091] Furthermore, the visibility of the boundary between the display area and the non-display area was evaluated for the above evaluation sample under fluorescent lighting. The evaluation criteria are as follows: [Evaluation Criteria] +2: The boundary is almost invisible. +1: Although there is improvement compared to Comparative Example 1, the boundary is still visible. 0: The difference in appearance between the display area and the non-display area (visibility of the boundary) is about the same as in Comparative Example 1. -1: The boundary is more visible compared to Comparative Example 1. -2: The boundary is clearly visible.

[0092] Table 1 shows the configuration and evaluation results of each optical laminate. [Table 1]

[0093] As shown in Table 1, when the optical laminate according to the embodiment of the present invention is used in an image display device, the color difference and reflectivity between the display area and the non-display area when the image is not displayed are reduced compared to the image display device of the comparative example, and good seamlessness is achieved. [Industrial applicability]

[0094] The optical laminate of the present invention can be suitably used in image display devices. [Explanation of Symbols]

[0095] 10. First polarizing plate 20. Second polarizing plate 30 printing layer 40 Adhesive layer 50 Surface base material layer 100 Optical laminate 110 Backlight Unit 120 Polarizing plate 130 LCD cells 140 Touch Panel 150 Organic EL elements 200 Image Display Devices

Claims

1. A first polarizer and a second polarizer, each containing a polarizer, are stacked such that the absorption axes of their respective polarizers are substantially parallel. A printed layer is provided along the outer periphery of the side of the first polarizing plate on which the second polarizing plate is arranged. The printed layer is a colored layer in the SCI L*a*b* color space, where L* is 50 or less, a* is between +10 and -10, and b* is between +10 and -10. Optical laminate.

2. The optical laminate according to claim 1, wherein the total light transmittance of the display area where the printed layer is not provided exceeds 35.0%.

3. The optical laminate according to claim 1, wherein the thickness of the printed layer is 3 μm to 30 μm.

4. The optical laminate according to claim 1, wherein the first polarizing plate and the second polarizing plate are bonded together via an adhesive layer.

5. The optical laminate according to claim 1, wherein a surface substrate layer is laminated on the side of the first polarizing plate opposite to the side on which the second polarizing plate is arranged.

6. The optical laminate according to claim 1, wherein a surface substrate layer is laminated on the side of the second polarizing plate opposite to the side on which the first polarizing plate is arranged.

7. An image display device comprising a display element and an optical laminate according to any one of claims 1 to 6, in this order toward the viewing side.

8. The image display device according to claim 7, wherein the SCI-based L*a*b* color difference (CIE 1976) between the portion on which the printed layer is provided and the portion on which the printed layer is not provided, as viewed from the viewing side when the image is not displayed, is less than 1.

5.

9. The image display device according to claim 7, wherein the reflectance of the portion on which the printed layer is provided, as viewed from the viewing side when it is not displayed, is 2.5% or less, according to the SCI method.

10. The image display device according to claim 7, wherein the display element includes a liquid crystal cell, an organic electronic element, or an inorganic electronic element.

11. The image display device according to claim 10, wherein the display element further includes a touch panel.

Citation Information

Patent Citations

  • Method for manufacturing protective sheet for liquid crystal display, protective sheet for liquid crystal display, method for manufacturing liquid crystal display device and liquid crystal display device

    JP2012230304A

  • Optical member and image display device

    JP2014238533A

  • Display body and adhesive sheet

    JP2020192708A

  • Composite polarizing plate and liquid crystal panel using same

    WO2017047407A1

  • Layered body and image display device

    WO2021145084A1